Digital-Based Performing Arts Event by the Semujo Community in the Pandemi Era in Jombang District - Nevi Carasavit Indah Permatasari; Eko Wahyuni Rahayu (Metafora: Education, Social Sciences and Humanities Journal, 2023)
Starting with the floods and landslides in early February 2021 in several areas in Jombang Regency, Novi Inggit Fitanaya sparked the idea of ​​holding the first digital art show during the pandemic to raise donations as well as a means of expression and displaying the works of artists. Interestingly, this event utilizes the YouTube Platform to organize these virtual shows as an effort to develop a digital-based show management system. This article aims to describe a digital-based Charity Show performance management system during the pandemic which was organized by the Jombang Young Artists Community named “Semujo”. The results of this research are expected to have use value and can be used to add to literature, knowledge, and insights for researchers, artists, and the general public. The research approach refers to the concept of performing arts management theory revealed by M. Jazuli. The research was carried out using descriptive qualitative research with data collection techniques through: observation, interviews, documentation, and literature study, and was supported using audio-visual recording equipment to document the data obtained. Data analysis techniques in this study were carried out through the stages of data reduction, data presentation, and drawing conclusions. Test the validity of the data using triangulation techniques including: method triangulation and source triangulation. The results of the study show that the Charity Show is an art performance event as the first social action in Jombang which is able to organize it in the midst of the Covid-19 pandemic with management that includes all elements of show management in the form of man, money, materials, machines, methods, and markets. Keywords: Charity Show, performing arts management, digital.